Rettelse til Grundtvig Studier 2000 - Lundgreen-Nielsen, Flemming; Michelsen, William; Bradley, S. A. J.; Pedersen, Kim Arne; Schjørring, Jens Holger (Grundtvig-Studier, 2002)
Corrections to Grundtvig Studies 2000